2022
DOI: 10.1029/2022gl100543
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol Formation Regulates Cloud Condensation Nuclei in the Global Remote Troposphere

Abstract: Formation of secondary organic aerosols (SOA) through the atmospheric oxidation of organic vapors has potential to enable particle growth to cloud condensation nuclei (CCN)‐relevant sizes. In this work, we constrain a global aerosol model by using aircraft measurements to reveal the global importance of SOA formation in CCN production. Our improved model, with explicit size‐resolved aerosol microphysics and parametrizations of semivolatile organic oxidation products, presents a state‐of‐the‐art performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The activation of aerosols into cloud condensation nuclei (CCN) and the subsequent cloud formation depend on their physical and chemical properties, including chemical composition, number concentration, size, mixing states, and prevailing atmospheric conditions (Andreae & Rosenfeld, 2008; Farmer et al., 2015; McFiggans et al., 2006 and references therein; Riemer et al., 2019). Recent studies from urban, rural, and remote locations have consistently underscored the influence of atmospheric chemistry on aerosol growth, composition, hygroscopicity, and mixing state, ultimately affecting CCN activity, although these parameters can be associated with different underlying mechanisms such as gas‐particle phase partitioning, heterogeneous chemistry, or multiphase chemistry (Kuang et al., 2021; Liu & Matsui, 2022; Slade et al., 2017; Tao et al., 2021; Zaveri et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of aerosols into cloud condensation nuclei (CCN) and the subsequent cloud formation depend on their physical and chemical properties, including chemical composition, number concentration, size, mixing states, and prevailing atmospheric conditions (Andreae & Rosenfeld, 2008; Farmer et al., 2015; McFiggans et al., 2006 and references therein; Riemer et al., 2019). Recent studies from urban, rural, and remote locations have consistently underscored the influence of atmospheric chemistry on aerosol growth, composition, hygroscopicity, and mixing state, ultimately affecting CCN activity, although these parameters can be associated with different underlying mechanisms such as gas‐particle phase partitioning, heterogeneous chemistry, or multiphase chemistry (Kuang et al., 2021; Liu & Matsui, 2022; Slade et al., 2017; Tao et al., 2021; Zaveri et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, exploring the water solubility characteristics of SOA with different aging degrees can help elucidate the more detailed extinction mechanism of SOA. In addition, recent studies have also shown that the formation of secondary particulates is one of the main processes determining the amount of CCN in remote oceanic regions (Liu and Matsui 2022). Therefore, investigating the water solubility of SOA with different aging degrees is also meaningful for further exploring its indirect climate effects.…”
Section: Introductionmentioning
confidence: 99%
“…The contrasting effects of nucleation on CCN at low supersaturations in model and observations is not explained in these previous studies. At the stage of particle growth, secondary organic aerosol (SOA) formed by atmospheric oxidation of organic vapors is a major contributor to particle growth to CCN-related sizes (Liu and Matsui, 2022;Qiao et al, 2021). SOA formed by multigenerational gas-phase oxidation of semi-volatile and intermediate volatility organic compounds (S/IVOC) is called SI-SOA (Jimenez et al, 2009;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%